A constituição de roteiros turísticos religiosos: um estudo de caso no caminho Padre João Schiavo (Caxias do Sul - RS) - Toigo, Gustavo Luis (My University, 2021)
This paper is aimed at the area of religious tourism. Specifically, to better make one acquainted with the officially created tour in the city of Caxias do Sul, in the Brazilian State of Rio Grande do Sul, in the year of 2016: The Father João Schiavo Route, henceforth identified by the acronym CPJS in Portuguese. This paper is qualitative in nature, it includes a real-life case and starts off with the following question: `How has CPJS come into being as a result of the established relations of the concerned social parties??. The script, from its inception until its touristic implementation in the city of Caxias do Sul has counted on the participation and involvement of the local government, the community, the religious congregation and the touristic sector. The main goal was to analyze the participation of social players and the relations established by them throughout the process of creating the CPJS touristic route as a boost for religious tourism in the city of Caxias do Sul. The theoretical framework includes religious tourism, touristic routes, stakeholders, planning and governance in tourism. The investigation encompassed documental and bibliographic research, as well as the use of questionaires with the stakeholders. The theoretical references have served as the reference for data analysis so as to understand how the social players acted to conceive the route and how relevant they were to the canonical process. Throughout this process, and in face of the performed analyses, it has been observed that Father Schiavo´s trajectory ended up serving as the reference point to create the tour. Based on the data collected from the questionaries, it has become obvious the importance of creating a governmental structure to better foster the participation of the main social parties in order to strengthen the administration, planning and implemetation of CPJS. As a result, tourism will grow, thus inceasing the potential of worshipping the religious figure, who, may soon be sanctified. [resumo fornecido pelo autor]
Este estudo volta-se ao segmento do turismo religioso para conhecer com mais profundidade um roteiro implantado por lei em Caxias do Sul/RS no ano de 2016: o Caminho Padre João Schiavo (CPJS). É uma pesquisa qualitativa com estudo de caso e que parte do seguinte questionamento: 'Como ocorreu o processo de constituição do CPJS, a partir das relações estabelecidas entre os atores sociais envolvidos?'. O roteiro, desde a origem até sua implementação turística no município de Caxias do Sul, contou com a participação e o envolvimento do poder público local, da comunidade, da congregação de religiosos e do trade turístico. O objetivo geral consistiu em analisar a participação dos atores sociais e as relações estabelecidas por eles no processo de formação do roteiro turístico CPJS como incentivo ao turismo religioso em Caxias do Sul. As bases teóricas utilizadas versam sobre turismo religioso, roteiro turístico, partes interessadas, planejamento e governança no turismo. A investigação abrangeu pesquisa bibliográfica e documental, além da aplicação de questionários com partes interessadas. O referencial teórico serviu de base para a análise dos dados com vistas à compreensão sobre como atuaram os atores sociais na concepção do roteiro e em suas relações com o processo canônico. Em meio a esse percurso e diante das análises realizadas, observou-se que a trajetória do padre Schiavo acabou sendo um fio condutor para a criação do roteiro. Com as informações obtidas nos questionários, constatou-se a importância de se instituir uma estrutura de governança para incentivar maior participação e adesão dos principais atores sociais para fortalecer a gestão, o planejamento e a implementação do CPJS. Isso tende a possibilitar crescimento no turismo, avançando no potencial de devoção do Beato que, em breve, poderá se tornar Santo. [resumo fornecido pelo autor]
Keywords: Turismo - Aspectos religiosos; Turismo - Caxias do Sul (RS); Peregrinos e peregrinações; Schiavo, João, Padre, 1903-1967 - Caxias do Sul (RS); Tourism - Religious aspects; Tourism - Caxias do Sul (RS); Pilgrims and pilgrimages